Weak Solutions for a Sixth Order Cahn-Hilliard Type Equation with Degenerate Mobility - Aibo Liu; Changchun Liu (Abstract and Applied Analysis)
We study an initial-boundary problem for a sixth order Cahn-Hilliard type equation, which arises in oil-water-surfactant mixtures. An existence result for the problem with a concentration dependent diffusional mobility in three space dimensions is presented.